Profile of Neonates Born to Mothers With COVID-19 at RSUD Haji in East Java - Noorvitry, Monique (Jurnal Medis Islam Internasional, 2022)
Background: COVID-19 infection can attack all levels of society, including pregnant women, which can impact the babies they give birth to and can increase morbidity & mortality in babies. Objective : This study was conducted descriptively & retrospectively. All the data were collected from inpatient medical records of patients in the COVID-19 neonatal isolation room at RSUD Haji Surabaya from January 1, 2021 - December 31, 2021. Methods: This study is retrospective and descriptive. The total population is all babies treated in the COVID-19 neonatal isolation room at the RSUD Haji Surabaya from January 1, 2021 – December 31, 2021. Data for all babies were obtained from medical records. Furthermore, the babies are grouped based on the way of birth. Furthermore, the baby's condition is broken down according to the required indicators. Results: Most of the babies of mothers with COVID-19 were born at full term spontaneously. Only three babies were born with severe asphyxia and needed CPR resuscitation and the help of CPAP or neopuff breathing apparatus. Only 4 of the 15 babies with positive PCR results. Conclusion: The vertical transmission of COVID-19 infection from pregnant women to their babies during the intrauterine period is still unclear because not all of these babies were confirmed for COVID-19 (the PCR results for these babies were only four positive). So further research is needed with larger samples and involving flashlights and other sectors related to COVID-19.